Efektivitas Modul Ajar Berbasis Literasi Sains Dalam Meningkatkan Keterampilan Analisis Peserta Didik Pada Materi Usaha, Energi, dan Pesawat Sederhana - Anugrah Yusuf; Helmi Abdullah; Firdaus Daud (Edukimbiosis: Jurnal Pendidikan IPA, 2026)
teaching module in improving students' analytical skills in the material of Work, Energy, and Simple Machines. The development of this module is motivated by the importance of analytical skills in physics learning and the need for teaching materials that are able to integrate scientific concepts with the context of everyday life. This study used a pre-experimental method with a one-group pretest-posttest design. The subjects of the study were all 38 students of grade VIII of SMP Al Qadri Islamic School Pinrang. Data collection was carried out through an analytical skills test given before and after the use of the module. The data obtained were then analyzed using a normality test, a paired samples t-test, and an N-Gain calculation to determine the level of improvement in students' abilities after participating in learning using the developed module. The results showed that the average score of students experienced a significant increase, namely from 54.36 in the pretest to 83.33 in the posttest. The percentage of learning completeness also increased from 10.53% to 65.79% after the use of the module. Furthermore, the N-Gain calculation result of 0.63 is in the moderate category, indicating an improvement in students' analytical abilities. Thus, the science literacy-based physics teaching module has proven effective as a teaching material to improve the analytical abilities and learning outcomes of eighth-grade students at Al Qadri Islamic School Pinrang Middle School..